Estudos biofísicos aplicados no mapeamento da interação entre compostos biologicamente ativos e macromoléculas - Silva, Marina de Magalhães (2020)
The understanding of action mechanism from molecules that bind to proteins, nucleic acids, carbohydrates, among others, is of the utmost importance since these biomolecules are involved in most cellular functions and the comprehension of their molecular target contribute to the development of new drugs. The aim of this work was to evaluate the interaction of different bioactive compounds with human hemoglobin (Hb) and ctDNA (Calf thymus) using spectroscopic techniques, electrophoresis and theoretical studies, which allowed investigate the binding magnitude of the complexes formed with protein and DNA. Thus, according to the results obtained it was observed that the pterocarpane derivative (LQB-223) formed a non-fluorescent supramolecular complex characterized by the static quenching mechanism and the binding constant (Kb) obtained was 1.94103 L mol-1 (30 °C), the hydrophobic interactions being responsible for stabilizing the complexes formed in this process. The binding mode was characterized by groove and by the electrophoresis assay, it was found that there was no DNA fragmentation. For the piperidine derivatives, it was observed that interaction occurs preferentially by static quenching, via intercalation, where Kb values ranged from 0.10 to 8.00104 L mol-1. By correlating the values of the binding constants with the biological activity data (GI50), it was observed that the correlation coefficients varied in the range of 0.8174  r  0.9868, for HT29, NCI-H460, 786-0 and NCI / ADR-RES, suggesting that the main mechanism of action of these compounds may be associated with DNA as a biological target. For the interaction studies between hemoglobin and thimerosal (TH), it was verified that the ligand interacts with the macromolecule by static quenching and binding constant about 106 L mol-1 and the main forces that govern this process are the electrostatics. The TH: Hb stoichiometry was 2:1, suggesting that ethyl mercury binding of thimerosal occurs in the two available cysteine residues (βCys93) present in the β subunit. These data are consistent with the results obtained by the NEM reagent (thiol group blocker) assay, where a decrease in Kb values was observed in the presence of increasing amounts of this reagent. In addition, it was found that conformational changes occur in the protein structure after complexation with the evaluated ligand being confirmed by the DLS and electrophoresis assays. In the competing species evaluation, it was observed that Ca(II) and Mg(II) were the ions that exerted the greatest influence on the interaction process. As consequence, inhibition of Hb-O2 binding capacity up to 72% (human Hb), and 50% (human erythrocytes), was verified. Dose-dependent induction of TH forming advanced glycation end products (AGE) and protein aggregates (amyloids) was additionally observed. Finally, these results highlight the toxic potential of the use of TH in biological systems, with a consequent risk to human health.